27. ANTIBIOTIC USE IN DA TON COMMUNE: INSIGHT EXPLORATION FROM PARENTS’ PERSPECTIVES (Vietnam Journal of Community Medicine, 2023)
Objective: This study aims to explore the reality of antibiotic use and its related factors in the community of parents in Da Ton Commune, Gia Lam District, Hanoi, Vietnam.Methods: Qualitative research method was conducted. In total, 10 parents meeting the selection criteria were randomly selected to be included in an in-depth interview.Results: More than half of the participants were concerned about the consequences of antibiotic misuse regarding diarrhea in children. Respiratory conditions were one of the most common reasons parents use antibiotics on their children. Risk factors causing antibiotic misuse included: easy access to antibiotics with low costs; lack of awareness of antibiotics and their consequences; lack of knowledge on seeking medical care and finding alternatives to antibiotics; and preference for pharmacist consultation. The community also utilized traditional and word-of-mouth medicine for healthcare purposes.Conclusion: After conducting interviews and engaging in discussions with individuals residing in Da Ton commune, the findings revealed a prevailing issue of antibiotic overuse, leading to frequent childhood diarrhea and enduring implications on their overall well-being. Through strengthening education and raising awareness appropriate to the cultural and economic environment of the community, children’s well-being can be significantly improved, contributing to a healthy community in the future.
Keywords: Antibiotics misuse, children, parents, qualitative research.